Elevating Writing Literacy Skills of Students of SMPN 48 Surabaya Through Writing Fables - Pasopati, Rommel Utungga; Kartiningsih, Rindrah; Wijaya, Kusuma; Sarmi, Ni Nyoman; Andharu, Devito; Fadillah, Muhammad Reza Ishadi; Agil, Agischa Putri; Wicaksono, Anggoro Cahyo (Gudang Jurnal Pengabdian Masyarakat, 2025)
This article explains the importance of writing fables, especially to improve writing literacy skills daily life imaginations. This writing is based on community service done to junior high school students in SMPN 48 Surabaya in 2024. The creative capacities of children possess the potential to enhance their comprehension of writing literacy skills through the act of writing fables. Through an exploratory approach within qualitative research, this manuscript underscores fable writing as a mechanism to cultivate literacy skills from describing, exploring, to explaining ideas from their minds to written fables. In conclusion, the practice of writing fables for junior high school students is essential to elevate writing literacy skills regarding the advancement of creativity in the students’ understandings of their everyday issues.